Selective monoalkylation of hydroquinone in the presence of SO3H-functionalized ionic liquids as catalysts - Bhongale, Priyanka V.; Joshi, Sunil S.; Mali, Nilesh A. (Chemical Papers, 2020)
A process aiming atO-alkylation of hydroquinone (HQ), where ionic liquids (ILs) act as catalyst is objectively described. Five SO3H-functionalized ILs having different cations were prepared and characterized by NMR and FTIR techniques. The acidity and thermal stability of ILs were determined by Hammett function and thermogravimetric analysis (TGA), respectively. The catalytic activity of these ILs were tested forO-alkylation of HQ with methanol in 4-methoxyphenol (4MP) in the presence of small amount of benzoquinone (BQ). The effect of reaction parameters such as temperature, time, catalyst loading and substrate concentration on the conversion of HQ and product distribution was examined and optimized to maximize the yield of 4MP using 1,3-disulfonic acid imidazolium hydrogen sulfate (IL2) catalyst. Maximum yield of desired product 4MP 93.79% was obtained at 338 K temperature, 5.45 x 10(-2) mol HQ, 8.33 x 10(-3) mol BQ, and 10.37 mol% catalyst loading in 120 min reaction time. Single-product formation was observed up to 338 K temperature but higher temperature (above 338 K) and longer reaction time resulted in the formation of 2,4-dimethoxyphenol (24DMP) as a by-product. Catalyst recyclability was also established up to the fifth run which showed no declination in its activity.
Keywords: 4-Methoxyphenol; Benzoquinone; Hydroquinone; ionic liquids; O-alkylation